Exploration of Innovation Strategies in Business Management: Enhancing Sustainability and Organizational Growth in the Digital Economic Era - Muhammad Saied*; Nila Atika; Sayudin Sayudin; Bahar Sagita; Aurelia Widya Astuti; Azka Muharram (Universitas Syiah Kuala, 2023)
In the era of a growing digital economy, companies are required to have a strong innovation strategy in order to survive and grow in a competitive environment. The purpose of this research is to explore innovation strategies in business management and understand the role of innovation strategies in improving organizational sustainability and growth in the digital economy era. This research uses a qualitative approach, while the data collection technique is done by literature study obtained from Google Schoolar. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and conclusion drawing. The results showed that companies in various sectors have a variety of innovation strategies in order to increase organizational sustainability and growth in the digital era, including organizations in the health sector, namely masks with product strategies, namely by creating unique mask motifs. Whereas in companies, innovation strategies in business management are carried out with product innovation, the use of external sources of innovation, and technology investment. In the banking sector, the strategy carried out in business management is a diversification strategy. In the creative and digital industries, innovation strategies focus on three main aspects, namely product innovation, process innovation, and marketing innovation. In addition, collaboration between marketing, engineering, and manufacturing is combined with agile management and agile manufacturing approaches. The synergy of these factors can achieve concurrent engineering (CE), which is an integrative approach to developing products simultaneously and efficiently.